A Case of Poly Drug Resistant –Tuberculous sternal osteomyelitis in an immunocompetent male - Syed, Beenish; Herekar, Fivzia (Infectious Diseases Journal of Pakistan, 2022)
Primary Sternal Tuberculosis is rare and accounts for < 1% cases of skeletal TB. Most cases are reported from TB endemic countries. Drug resistant sternal tuberculosis has been sporadically reported in literature. We present here a case of polydrug resistant Tuberculosis of sternum in an immunocompetent male. AFB culture showed resistance to Streptomycin(S) and Isoniazid (H). Patient was started on modified ATT with HREZ + Levofloxacin + Amikacin. Total duration of treatment was 10 months. Poly drug resistant TB can lead to amplification of resistance and MDR - TB on treatment with the standardized 1st line drugs. DST results at baseline and previous treatment history should be considered to design the appropriate regimen. At least 3 or 4, likely effective drugs should be selected for duration of 9-18 months. Key words: Amplification of resistance, Drug sensitivity testing, Treatment failure